Modeling the Effects of Seasonal Fishing Moratorium on the Ecosystem of the Minjiang Estuary in Southeastern China - Kong, Yefu; Kang, Bin; Shi, Xiaotao (Frontiers in Marine Science, 2022)
China’s marine fisheries have made a huge contribution to the world's food supply at the expense of wild resources collapse by overfishing. Accordingly, the government has introduced a series of measures represented by seasonal fishing moratorium to achieve sustainable fisheries. To evaluate the impact of the seasonal fishing moratorium on the ecosystem of the Minjiang Estuary in southeastern China, three ecosystem models, one in 2006, one in 2016 after ten years seasonal fishing moratorium, and one in simulated 2016 under the scenario without fishing moratorium, were constructed by Ecopath with Ecosim. Based on 2016 model, the status of the Minjiang Estuary ecosystem after fifty years was simulated under four scenarios of different combinations of fishing pressure and durations of the fishing moratorium. The results showed that in 2016 model, parameters as total ecosystem flow, mean fishing trophic level, and Finn's index were 9235.407 t·km-2·year-1, 2.94, and 0.920, respectively, all significantly higher than those extracted from simulated 2016 model, suggesting the effectiveness of seasonal fishing moratorium. Under scenario analysis, extending the fishing moratorium by three months and reducing fishing pressure by 50% showed synergistic effects to achieve a better result than the current fishing moratorium strategy.